The influence of perceived ease, trust and promotion on decisions use of OVO Apps - Linda Veny Viliana; Basar Maringan Hutauruk (Institute of Computer Science (IOCS), 2023)
This study aims to determine the effect of perceived convenience, trust, promotion on the decision to use the OVO application. The sample in the study was 100 people with a population of Pelita Bangsa University students who made transactions using the OVO application. Data collection techniques include observation, distribution of questionnaires and literature study. The type of research used is quantitative. The analytical method used is validity test, reliability test, classical assumption test, multiple linear analysis and hypothesis testing. The results of the study stated that the perceived ease of use partially had a negative and insignificant influence on the decision to use because the calculated t value was smaller than t table and the sig value was greater than 0.05. Partial trust also has a negative and insignificant effect on the decision to use because the calculated t value is smaller than t table and the sig value is greater than 0.05. Meanwhile, promotion has a positive and significant influence on the decision to use, which means that the better the promotion, the decision to use OVO also increases. Simultaneously the perception of ease, trust and promotion influence the decision to use.